2009
DOI: 10.2353/ajpath.2009.090035
|View full text |Cite
|
Sign up to set email alerts
|

Role of MKP-1 in Osteoclasts and Bone Homeostasis

Abstract: Bone mass is maintained through the complementary activities of osteoblasts and osteoclasts; yet differentiation of either osteoblasts and osteoclasts engages the mitogen-activated protein kinase (MAPK) pathway. The MAPKs are negatively regulated by a family of dual-specificity phosphatases known as the MAPK phosphatases (MKPs). MKP-1 is a stress-responsive MKP that inactivates the MAPKs and plays a central role in macrophages; however, whether MKP-1 plays a role in the maintenance of bone mass has yet to be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 30 publications
8
32
0
Order By: Relevance
“…Previous work by others has established that Dusp1 deficient mice have a smaller skeletal phenotype compared to matched WT littermates [37]. Interestingly, our group has also showed that deletion of Dusp-1 resulted in less OC as a result of reduced Vitamin D-induced RANKL expression in bone marrow stromal populations due to impaired RXR/VDR heterodimer nuclear translocation [38].…”
Section: Discussionmentioning
confidence: 64%
“…Previous work by others has established that Dusp1 deficient mice have a smaller skeletal phenotype compared to matched WT littermates [37]. Interestingly, our group has also showed that deletion of Dusp-1 resulted in less OC as a result of reduced Vitamin D-induced RANKL expression in bone marrow stromal populations due to impaired RXR/VDR heterodimer nuclear translocation [38].…”
Section: Discussionmentioning
confidence: 64%
“…Our study emphasized the important role of MKP-1 in maintaining bone homeostasis, suggesting the potential therapeutic effects of MKP-1 gene transfer in diseases associated with inflammatory bone loss. A recent study showed that MKP-1 KO mice had equivalent bone loss, but fewer osteoclasts compared with WT mice after ovariectomy 34 . Instead they showed that osteoclasts from MKP-1 KO mice had higher resorptive activity than osteoclasts from WT mice.…”
Section: Discussionmentioning
confidence: 98%
“…It is a negative regulator of innate and adaptative immunity, it plays an important role in metabolism, potentially a pathophysiological role in the progression of obesity and metabolic syndrome and is a regulator of bone mass as well [31], [44]. Actually, the lack of MKP-1 is associated with a reduced trabecular bone density in female mice [45], [46]. In vivo , Carlson et al demonstrated that MKP-1 negatively regulates osteoclast differentiation and activation in response to LPS injection.…”
Section: Discussionmentioning
confidence: 99%